حقوق مجردہ کی معاصرتطبیقات کاتعارفی جائزہ - Muhammad Amjad; Hafiz Nasir Ali (Pakistan Journal of Islamic Research)
This article is an attempt to discuss and analyze the concept of exclusive rights in Islamic Fiqh with its various kinds and their implementation in contemporary age. Exclusive rights are those rights that are free from ownership and they do not have a consistent connection with the place (physical things). If those rights are used or left, there is no effect on the place (physical things). Exclusive rights have a lot of types that can be summarized as follows: (1) Necessary rights, meaning those exclusive rights that are stipulated to avoid harm like pre-emption rights and right of a wife for her turn in the husband spending the night with her. (2) The right to share like passing rights, [the new type is flight right and road tax] right of elevation [the new type is the elevation of towers], equitable (water stream) rights [the new type is pipeline and small wells], executor’s (passing) rights [new type is gas pipe line], drinking ( field watering) rights [new type is water supply and gas supply], the right of benefiting from neighbor( a wall) (3) transaction rights like haqqe wazaif (services right) and haqqe khalw (evacuation right)  (4) precedence and specialty rights like immigration (marking boundaries) rights and from its contemporary types, authoring rights, publishing rights, privilege rights, trade name and trademark, trade license etc.